2014
DOI: 10.3906/biy-1404-104
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs and cancer

Abstract: IntroductionFollowing the completion of the human genome a decade ago, we came across a surprisingly low number of proteincoding genes in the human genome compared to the initial predictions. The low number of protein-coding genes, corresponding to only 2% of the human genome, was surprising, because it meant that we were undervaluing the potential roles of alternative promoter usage, alternative splicing, alternative polyadenylation, and so on to explain the vast diversity of proteins in cells. It was also a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…miRNAs are putative translational regulatory gene family [2]. It is belief to actively involved in the post-transciptional process by regulating the expression of half of the genes in a cell [7]. A recent report by Zou [8], suggested that destabilizating a target miRNA greatly reduced the protein levels of a cell [9].…”
Section: Micrornasmentioning
confidence: 99%
“…miRNAs are putative translational regulatory gene family [2]. It is belief to actively involved in the post-transciptional process by regulating the expression of half of the genes in a cell [7]. A recent report by Zou [8], suggested that destabilizating a target miRNA greatly reduced the protein levels of a cell [9].…”
Section: Micrornasmentioning
confidence: 99%
“…In addition, the number of lncRNA transcripts exceeds the number of genes, since a gene may be template for several different splice variants of a lncRNA (Melissari and Grote 2016). www.iiste.org An accepted classification system of lncRNAs is a system based on their location; intergenic, intronic, antisense chain or upstream of protein-coding genes are named according to their presence (Akman andBensan 2014, Bär andThum 2016). Sense RNAs are transcripts that overlap the coding gene within an intron on the same chain.…”
Section: Lncrnas and Their Biogenesismentioning
confidence: 99%
“…LncRNAs are >200 nt long transcripts bearing null to scant protein-coding capacity (Qi & Du, 2013). They are transcribed by RNA polymerase II (RNA Pol II), spliced, and polyadenylated into short exonic segments (Bartonicek et al, 2016;Tuncer & Bensan, 2014). The increasing number of lncRNAs discovered in the genomes of complex organisms suggests their involvement in development, dosage compensation, imprinting, and organogenesis.…”
Section: Introductionmentioning
confidence: 99%